ANALISIS FAKTOR RESIKOKANKER LEHER RAHIM PADA WANITA DI RSUD Prof. Dr. MARGONO SOEKARJOPURWOKERTOTAHUN 2011 - Feti Kumala Dewi; Fitri Nurhayati (Universitas Harapan Bangsa Purwokerto, 2011)
Cervical canceris influencedby severalfactorsincludingtherisk offirst sexualactivity, age,parity, smoking, use ofcontraception. Cervicalcancer casesin hospitalsProf. Dr.MargonoSoekarjoPurwokertoIn 2011as many as273 women.To determine the relationshipofrisk factorsof cervical cancerin women withcervicalcancer incidencein hospitalsProf. Dr.MargonoSoekarjoNavanin 2011. The research method isdescriptivecorrelationwithretrospective approachusingsecondarydatawith thepopulation ofwomen suffering fromcervical canceras many as273women, usingasampling techniquequatasamplingwith a sample of100 women. The instrument usedwasachecklist. Analysis usingkendall'stautestandlinearregression. The results showedthe classification ofmostcervicalcancerhadstage III cancerby48respondents(48%), there is a relationshipbetween theage oftheincidenceof cervicalcanceristhe value ofP=0.001 (P <0.05). There was no associationbetweenparitywith the incidenceofcervicalcancer isthe value ofP=0.539(P>0.05). No associationwithcontraceptivecervicalcancerP =0.064(P>0.05). Based onmultiple linear regression analysiswith the resultsofage(p=0.001), parityfactor(p=0.740), and afactor ofcontraception(p=0.065), indicating theage factoristhe mostdominantfactoraffectingcervical cancer. From theresults of the studyshowed thatthe risk factorsof agehave the most impacton theincidence ofcervical cancerin women. Keywords: riskfactors, women cervical cancer.